Los jueces de paz y su intervención en conflictos cotidianos: conciliaciones, demandas y sentencias. Rosario (Argentina) 1854-1872 - Evangelina De los Ríos (Nuevo mundo - Mundos Nuevos, 2020)
This article proposes to study the ways in which the justices of the peace administered justice in the urban environment of the city of Rosario between 1850 and 1870. It will show how these judges embodied mediation and social ordering "face to face" with the population of their barracks through the extensive correspondence they kept with different local authorities (Political Chief, Chief of Police and Judge at the Court of First Instance). The documentation allows to retrieve the cases presented to the court, the ways in which these judges solved the conflicts and the grounds on which they issued their sentences.